Enhancing Financial Literacy - Financial Access (2020)
The performance of micro, small and medium enterprises (MSMEs) in markets and socio-political arenas – and their ability to have a voice — is essential for achieving sustainable landscapes that are resilient to external shocks, such as changes in markets, policy or climate. To strengthen both the performance and voice of MSMEs they need to have access to resources, including finance. One of the main barriers to access finance for MSMEs is lack of financial literacy. This publication presents a review of experiences and proposes a strategy to strengthen the financial literacy of MSMEs in the landscapes and value chains where TBI and its partners work.